New application of ombuoside in protecting auditory cells from cisplatin-induced ototoxicity via the apoptosis pathway - Xingxing Wu; Xixia Peng; Yue Zhang; Wanjun Peng; Xiaochan Lu; Tingting Deng; Guohui Nie (Heliyon)
Hearing loss is caused by many factors including ototoxic drug-induced hair cell damage. Ombuoside, an antioxidant isolated from Gynostemma pentaphyllum, has been suggested to serve as a new neuroprotective drug. However, the role of ombuoside in protecting inner ear hair cells from ototoxic drug-induced damage has not been investigated. Here, we demonstrated the protective potential of ombuoside in mitigating drug-induced ototoxicity in vivo and in vitro. We used cisplatin, a highly ototoxic anti-tumor drug, to induce hair cell damage. Our results showed that ombuoside significantly increased the survival of cisplatin-treated HEI-OC1 cells. Further mechanism research suggested that ombuoside protects HEI-OCI cells from cisplatin-induced apoptosis by reducing the cisplatin-induced upregulation of apoptosis-promoting proteins Bax, Bak, as well as apoptosis indicator proteins cytochrome C and cleaved-caspase-3, and the downregulation of apoptosis-inhibiting proteins Bcl-2. Ombuoside also protects the cells from the excessive ROS production and mitochondrial membrane depolarization triggered by cisplatin. These results demonstrated the potential for ombuoside in protecting hair cells from cisplatin by suppressing ROS generation and the mitochondrial apoptotic cascade. Ombuoside showed promise in protecting hair cells from cisplatin-induced apoptosis by suppressing ROS generation and the mitochondrial apoptotic cascade. Furthermore, ombuoside co-treatment in mouse cochlear explants and zebrafish lateral neuromasts rescued the decreased number and deformed morphology of hair cells resulting from cisplatin exposure. These findings further validated our conclusions and indicated that ombuoside is a potential protector against hearing loss caused by ototoxicity as a clinical side effect of cisplatin.